Force generation profiles of para-Nordic sit-skiers representing different physical impairments - Karczewska-Lindinger, M.; Linnamo, V.; Rosso, V.; Gastaldi, L.; Rapp, W.; Vanlandewijck, Y.; Lindinger, S. (Journal of Science in Sport and Exercise, 2021)
Purpose: To biomechanically profile force generation connected to the complex role of the trunk in double poling in a representative sample of Para-Nordic sit-skiers. Methods: Twelve male World Cup Para-Nordic sit-skiers (sport classes: LW10-12) were skiing on flat snow terrain at submaximal speed of 4.5 m/s (~ 73% maximum speed). 2D video (50 Hz) and pole force analyses (1000 Hz) were performed synchronously, examining angle, force and cycle characteristics to analyse the role of the trunk in generating propulsion. Results: LW10-11.5 skiers lost between 21% and 4% propulsive force versus LW12 athletes only due to different geometrics of the trunk and pole angle at an equal axial pole force. While LW10-11 skiers indicated trunk extension or position maintenance during pole thrust, LW11.5-12 skiers showed strong trunk flexion combined with smaller pole angles to the ground. Hence, LW11.5-12 skiers could create larger propulsive forces and therefore greater cycle lengths at lower cycle rates at the same speed. Maximum speed increased from LW10 to LW12 and was significantly correlated to trunk flexion range of motion (r = 0.63) and cycle length (r = 0.59). Trunk flexion ROM showed a significant relationship to the impulse of propulsive force (r = 0.63) and pole angle to the ground (r = - 0.76) (all P < 0.05). Conclusion: The impact of impairment on the force production profiles and its physiological-biomechanical consequences need further investigation also in other terrains and at wider spectrums of skiing speeds. The evident problem of low numbers of LW10-11 skiers in World Cup needs creative future solutions for research.